Continuous and non-invasive thermography of mouse skin accurately describes core body temperature patterns, but not absolute core temperature - van der Vinne, Vincent (Sci Rep, 2020)
Body temperature is an important physiological parameter in many studies of laboratory mice. Continuous assessment of body temperature has traditionally required surgical implantation of a telemeter, but this invasive procedure adversely impacts animal welfare. Near-infrared thermography provides a non-invasive alternative by continuously measuring the highest temperature on the outside of the body (T(skin)), but the reliability of these recordings as a proxy for continuous core body temperature (T(core)) measurements has not been assessed. Here, T(core) (30 s resolution) and T(skin) (1 s resolution) were continuously measured for three days in mice exposed to ad libitum and restricted feeding conditions. We subsequently developed an algorithm that optimised the reliability of a T(skin)-derived estimate of T(core). This identified the average of the maximum T(skin) per minute over a 30-min interval as the optimal way to estimate T(core). Subsequent validation analyses did however demonstrate that this T(skin)-derived proxy did not provide a reliable estimate of the absolute T(core) due to the high between-animal variability in the relationship between T(skin) and T(core). Conversely, validation showed that T(skin)-derived estimates of T(core) reliably describe temporal patterns in physiologically-relevant T(core) changes and provide an excellent measure to perform within-animal comparisons of relative changes in T(core).